Three-pronged (3P) Approach to Strengthen Feedback Mechanism in Engineering Education - Khurana, Meenu; Manuja, Manoj (Journal of Engineering Education Transformations, 2023)
Effectiveness in teaching-learning process and attainment of program outcomes are the areas for which educational institutes are largely accountable. Internal feedback mechanism is the key to enhance the quality of teaching-learning process thereby contributing towards attainment of program outcomes and hence important for the growth of institute. This mechanism should be strong enough for receiving adequate information from stakeholders to help in tweaking or improving the processes. Feedback from students has been a common mechanism being followed in the educational institutes. Also, the industry feedback is considered for curriculum revision. In this paper we will discuss about three pronged (3P) approach for such a feedback mechanism. Three prongs in this approach are the closed loop feedback mechanism, sensitizing students about the importance of feedback and agility in feedback process. Designing feedback and analyzing the feedback received from all the sources in tandem is the backbone of this approach and has been discussed in detail in this paper. The paper presents case study of implementation of proposed 3P approach to enhance the students' learning of computer programming course.